An Implicit Algorithm for the Split Fixed Point and Convex Feasibility Problems - Fengjun Guo; Shin Min Kang; Young Chel Kwun (Abstract and Applied Analysis)
We consider an implicit algorithm for the split fixed point and convex feasibility problems. Strong convergence theorem is obtained.